Percutaneous coronary intervention-associated Actinomyces oris - Walaa Saeed (17100163) (2020)
Coronary artery interventions are safe procedures yet have a risk of stent infection, bacteremia and sepsis, events that are rare but with high morbidity and mortality sequel. A few prior cases had reported post percutaneous coronary intervention (PCI) infections, abscesses and sepsis due to Staphylococcus aureus, followed by Pseudomonas aeruginosa. Cardiac Actinomyces infections are extremely rare. Here we report a case of a 50 year old patient who developed a post intervention Actinomyces oris epicardial abscess occluding right coronary artery with subsequent bacteremia eventually requiring open heart surgery. He was treated during and thereafter with IV penicillin and ceftriaxone for almost 8 weeks. We highlight during this review the available literature regarding risk factors, the possible theories of acquiring such bacterium at this unusual site as well as our patient’s course and treatment outcome. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00929